2010
DOI: 10.1093/humrep/deq020
|View full text |Cite
|
Sign up to set email alerts
|

The role of Foxp3+ regulatory T-cells in endometriosis: a potential controlling mechanism for a complex, chronic immunological condition

Abstract: We propose that in eutopic endometrium in women with endometriosis Foxp3+ cells decrease the ability of newly recruited immune cell populations to effectively recognize and target endometrial antigens shed during menstruation, allowing their survival and ability to implant in ectopic sites. At these ectopic sites, variable expression of Foxp3+ cells within some peritoneal endometriotic lesions is likely to be linked to the characteristics and stage of individual lesion development and be playing key roles in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
114
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(126 citation statements)
references
References 44 publications
8
114
2
2
Order By: Relevance
“…The density of endometrial Foxp3 + regulatory T cells rose gradually throughout the proliferative phase. 54 The authors suggested that the increase in peripheral blood and endometrial Foxp3 + regulatory T cells may play a role in the implantation of an embryo in the mid-secretory phase.…”
Section: Human Regulatory T and Th17 Cells During A Menstrual Cycle Amentioning
confidence: 99%
“…The density of endometrial Foxp3 + regulatory T cells rose gradually throughout the proliferative phase. 54 The authors suggested that the increase in peripheral blood and endometrial Foxp3 + regulatory T cells may play a role in the implantation of an embryo in the mid-secretory phase.…”
Section: Human Regulatory T and Th17 Cells During A Menstrual Cycle Amentioning
confidence: 99%
“…Patients with endometriosis have elevated levels of immune mediators in the peritoneal fluid, which is believed to occur as a result of improper ectopic tissue clearance [13][14][15]. Women with endometriosis have been shown to have reduced T regulatory cell populations in both the periphery and within the endometrium [16], as well as increased T regulatory cells in ectopic endometrial tissue [17], creating an immunosuppressive microenvironment that allows for endometriotic lesions to survive. Together, these data suggest endometriosis may be characterized as an immune disorder with autoimmune and chronic inflammatory tendencies.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Endometriosis is an inflammatory condition, and mounting evidence suggests that dysregulated immune and other responses within the eutopic endometrium are likely to precede well-documented changes at ectopic sites. [5][6][7][8][9][10][11] Investigating immunological responses within the uterine-and lesiondraining lymph nodes (LNs) should be important in terms of trying to understand endometriosis pathophysiology. Endometriosis has invasive characteristics as endometrial tissue must attach to and invade the peritoneum, establish a blood supply, and continue to proliferate to form an ectopic lesion.…”
Section: Introductionmentioning
confidence: 99%